GAPURA WRINGIN LAWANG SEBAGAI IDE PENCIPTAAN KARYA SENI MACRAMÉ - Ninik Juniati; Ardeliah Tjiptawan (Jurusan Seni Rupa ISBI Bandung, 2019)
Wringin Lawang gapura (gate) is the entrance of all temples in Trowulan region in Mojokerto. It is unique since it is layered and made entirely of red bricks. The brick arrangement detail of the gapura is an artistic inspiration for a macramé artwork. The purpose of this study is to combine elements of a local genius in the form of a typical East Java temple gate and an ancient art originated in Near Eastern Origin region in the form of a wall hanging macramé. Overall the finished work is consistent with its design in terms of the amount of detail and parts of the macramé such as the layers. Thus, to overcome the shortcomings of the macramé, adding knot details to the tighter layers and or adding material such as beads or other materials that match the inspiration in the middle of the cord span to reduce the asymmetrical form of detail. A rip effect made the cord span more stable. Keywords : Wringin Lawang Gapura, Macramé, Wall Hanging___________________________________________________________________ Gapura Wringin Lawang merupakan pintu masuk dari semua candi yang ada di kawasan Trowulan, Mojokerto. Dia memiliki keunikan dari bentuk bertingkat-tingkat dan terbuat dari batu bata merah. Detail susunan batu bata pada gapura inilah menjadi inspirasi sebagai ide penciptaan karya seni macramé. Tujuan karya ini untuk memadukan unsur kearifan lokal bentuk gapura candi khas Jawa Timur dengan teknik macramé yang ada pada peradaban kuno Mesopotamia, Mesir kuno dan sekitarnya dengan bentuk wall hanging. Hasil karya ini disesuaikan dengan konsep desain secara detail dengan bagian-bagian seperti undakan. Material tambahan diletakkan di tengah bentangan tali untuk mengurangi bentuk detail yang tidak simetris, meminimalisir efek koyakan, sehingga membuat bentangan tali menjadi lebih stabil.Kata Kunci: Gapura Wringin Lawang, Macramé, Hiasan Dinding